Virasaivism and Christianity: A Dialogue on Doctrines - Madtha, William (Journal of Dharma, 1983)
In the technological world of today man has been overwhelmed by the tremendous progress of positive sciences, which have enabled him to release his hitherto dormant powers. Thanks to them, he has not only created machine after his own image but even succeeded in fluttering in space and even landing on the moon on the other hand, as a consequence of this scientific progress, he has many things to dabble in and therefore finds no leisure to spend serious thought on non-scientific aspects of life. One of the greatest failures of modern man is his apathy towards things spiritual. He fails miserably when It comes to giving thought to the very meaning of his own existence or of his society. This neglect constitutes a real threat to his progress. r he consequences of this threat, which is not only radical but also evil, are numerous. They can be, however, grouped under two main evils of the day : the dehumanization of man, and the desacralization of religion.